Compassion fatigue and posttraumatic stress disorder symptoms suffered by professionals treating victims of gender violence - Lucas Arranz, Miriam; Rossi Freducci, Diletta (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2023)
Compassion fatigue is a term to describe the emotional, physical and psychological consequences of helping others. It mainly appears in jobs related to humanitarian assistance. The main aim of this article is to investigate the specific effects of working with victims of gender violence in these professionals.Three different research lines have been established: the first one of how working in gender roles affects their private life (two study samples have been compared: the first one made up of 80 gender specialists and the other one of 80 women who carry out their jobs in other areas), the second one about vicarious trauma and the third one referred to the discomfort caused by precariousness in psychosocial intervention. The outcomes show the following conclusions: 1) Gender experts suffer more negative effects when they face situations in their private life related to gender problems compared with the general population. 2) The majority of the professional interviewed suffered secondary post-traumatic stress symptoms as a result of working in violence. Social workers show the highest rate of symptoms, followed by psychologists and educators, educational assistants and administratives.3) The 78,7% of the psychosocial professionals group think that there is a lack of economical reward for their activity.This article also analyzed the fact that the topic ´gender´ arises frequently in their daily life, making difficult to disconnect from work.
Keywords: Compassion fatigue; Occupational risks; Gender violence; Vicarious trauma; Selfcare